Edifice and education: structuring thought in twelfth-century Europe - Kinsella, K (2015)
This thesis explores the diverse range of textual and visual architectural representations in twelfth-century didactic texts. It argues that these representations are not arbitrarily chosen frameworks for holding data; instead, architecture can perform a certain pedagogical role. In this role architectural representations mediate between imperceptible abstract concepts in the text and the tangible world of the reader. By focusing on the relationship between text and image this thesis argues that the two play a meaningful part in conveying intangible elements of the world to the reader. The thesis creates an alternative to the historiography on architecture and its representations by redirecting focus from the development of technical drawings and onto the intellectual context of the drawings, and ultimately questions why architecture, in particular, appears so frequently in didactic manuscripts of the period. The argument is framed by two points. First, it recognises the manifold ways in which architectural representations appear by focusing on three particular examples: quadrivial texts, Richard of Saint Victor's In visionem Ezechielis, and Honorius Augustodunensis' Gemma animae. These texts provide case studies to argue the primary point of thesis, namely, that architectural representations were used to provide tangible or kinaesthetic models to aid readers' understanding of difficult material. Second, the language and structure of the three studies reflect a dimensional framework that was used to articulate particular aspects of the drawings. The dimensional aspects of the drawings appear in texts as references to length, width, height, and the typological qualities of architecture. Overall the thesis has two important implications. First by recognising the important relationship between text and image it is possible to draw out the pedagogical aims and processes present in some twelfth-century didactic works. Second, common examples of architectural representations, such as Gospel canon tables, are recognised as part of a broader spectrum of heuristic images and diagrams.